Private Providers of Higher Education in the UK - Fielden, John (International Higher Education, 2010)
A recent research report from Universities UK has analyzed the growth of private providers of higher education in the United Kingdom and questioned whether they are a threat to the publicly funded sector. Private providers form a mixed group, and it is impossible to generalize about them. In any event the coming years are sure to see a continuing growth in private provision for both domestic and international students.